Incidental lowering of otitis-media complaints in otitis-prone children during COVID-19 pandemic: not all evil comes to hurt - Torretta, Sara (Eur J Pediatr, 2020)
Given COVID-19 pandemic periodic outpatient assessment of otitis-prone children regularly followed at our tertiary outpatient clinic of upper respiratory tract infections was discontinued since 9 March. In order to avoid leaving the patients to themselves just during the winter months, which are the most critical ones for these children, we kept in touch with the families of 102 children (mean age 41.4 ± 14.0 months) who had had a follow-up visit scheduled during the lockdown, and compensated with telemedicine assessment. This incidentally leads to the unexpected but not at all negative finding that a consistent clinical improvement had been occurred in most (82.3%) of children. A statistically significant reduction in the mean number of documented acute otitis media episodes, otorrhea episodes, and systemic antibiotic treatments during the February–April 2020 period compared with February–April 2019 was attested. Clinical evaluation performed in 27.4% cases revealed normal middle ear findings in all but three (89.3%) children. Conclusion: Our data document a global improvement of otitis-prone children in Milan during the Italian lockdown, as a fortuitous and incidental positive effect of the national lockdown.